Implementasi Kebijakan Penyediaan "Rumah Perlindungan Pekerja Perempuan (RP3)" di Tempat Kerja - Ayu Sofia Rahmi; Ida Widianingsih; Erna Herawati (Jurnal Ilmiah Administrasi Publik, 2025)
This research aims to find out how the policy implementation of the policy of Ministry of Women’s Empowerment and Child Protection Regulation Number 1 of 2013 concerning Providing House of Women Workers Protection in the workplace. This policy is government effort to protect female workers. This research uses theoretical concept of Syahrul Mubarok (Policy Analysis Triangle Framework) which was carried out using qualitative methods through interview at the Ministry of Women’s Empowerment and Child Protection of Indonesia, IndustriALL Indonesia Council Women's Committee and the head of House of Women Workers Protection in PT. Evoluzione Tyres. The result illustrates that policy implementation which carried by top-down faces an obstacle that provision by coordinating with related agencies has sectoral egos. However, the implementation of this policy can be done in companies by implementing bottom-up, building collaboration with IndustriALL so that the policy implementation has achieved by providing the House of Women Workers Protection in PT. Evoluzione Tyres.